La negociación como proceso - Castellanos Herrera, Silvio José (2021)
Negotiation is an activity inherent to the human being, which is carried out practically on a daily basis, even if it is not consciously internalized. In this sense, this work aims to strengthen the idea that the negotiating technique should be addressed in political, judicial and extrajudicial environments as an ideal means for the resolution of conflicts of various kinds, mainly in those where the State plays a fundamental role, as the main interest in peace, in providing for its legal order, all the mechanisms that facilitate the desidertum of a harmonious coexistence, in the context of a social contract.   For this will show how discipline arises, in a transit that goes from the "Game Library", through the "Decision Library", to reach synergistically a methodology that must be contemplated in an inessible way, in every conflict addressed by man. In this sense, as a methodology we will address the bibliographic revision in its aspects, constitutional, doctrinaus and legal, in order to reach conclusions aimed at achieving justice and social balance, because, as a method, it allows the promotion of concerts that enable, for the parties, the achievement of their aspirations rationally.